Human Rights Implications of Tax Validation Policies on Land and Building Sales: A Social Justice Perspective - Lilik Warsito (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
One of the taxable objects is the transfer of rights over land and/or buildings. Land and buildings gain value as they can be transferred from their owners to others who desire them. The taxable object of the transfer of rights over land and/or buildings is subject to taxes from both the seller and the buyer. The seller is subject to income tax (PPh), while the buyer is subject to a tax in the form of a duty on the acquisition of rights over land and buildings (BPHTB). The taxable object of the duty on the acquisition of rights over land and buildings includes land, buildings, as well as land and buildings. This analysis examines land procurement from a Human Rights perspective. The fundamental values of Human Rights should underlie development, as there is a close connection between development and Human Rights. The quality of life of the affected community must be improved or at least remain the same as before the land acquisition. Land procurement activities should also accommodate the protection of the rights and interests of the community, including the right to receive welfare guarantees so that they do not become poorer than before their land was acquired. The principles of taxation that are universally recognized, namely justice, convenience, and administrative efficiency, as well as the enhancement and optimization of state revenue, should be upheld while maintaining self-assessment.